Cell communication and relevant signaling pathways in osteogenesis–angiogenesis coupling - Shuqing Li; Xinjia Cai; Jiahe Guo; Xiaolu Li; Wen Li; Yan Liu; Mengchun Qi (Bone Research)
Abstract Osteogenesis is the process of bone formation mediated by the osteoblasts, participating in various bone-related physiological processes including bone development, bone homeostasis and fracture healing. It exhibits temporal and spatial interconnectivity with angiogenesis, constructed by multiple forms of cell communication occurring between bone and vascular endothelial cells. Molecular regulation among different cell types is crucial for coordinating osteogenesis and angiogenesis to facilitate bone remodeling, fracture healing, and other bone-related processes. The transmission of signaling molecules and the activation of their corresponding signal pathways are indispensable for various forms of cell communication. This communication acts as a “bridge” in coupling osteogenesis to angiogenesis. This article reviews the modes and processes of cell communication in osteogenesis-angiogenesis coupling over the past decade, mainly focusing on interactions among bone-related cells and vascular endothelial cells to provide insights into the mechanism of cell communication of osteogenesis-angiogenesis coupling in different bone-related contexts. Moreover, clinical relevance and applications are also introduced in this review.